Forecasting Austrian IPOs: An application of linear and neural network error-correction models - Christian Haefke; Christian Helmenstein (Institute for Advanced Studies (IHS), 1995)
In this paper we apply cointegration and Granger-causality analyses to construct linear and neural network error-correction models for an Austrian Initial Public Offerings IndeX (IPOXATX). We use the significant relationship between the IPOXATX and the Austrian Stock Market Index ATX to forecast the IPOXATX. For prediction purposes we apply augmented feedforward neural networks whose architecture is determined by Sequential Network Construction with the Schwartz Information Criterion as an estimator for the prediction risk. Trading based on the forecasts yields results superior to Buy and Hold or Moving Average trading strategies in terms of mean-variance considerations. – – In dieser Arbeit verwenden wir Kointegrations- und Granger-Kausalitätsanalysen, um lineare und konnexionistische Fehlerkorrekturmodelle für den österreichischen Erstemissionsindex (IPOX ATX) zu spezifizieren. Wir verwenden die signifikanten Abhängigkeiten zwischen IPOX ATX und dem repräsentativen ATX (Austrian Traded Index), um den IPOX ATX zu prognostizieren. Wir ermitteln die optimale Architektur des feedforward Netzwerkes durch sequentielle Netzwerkkonstruktion wobei das Informationskriterium von Schwartz als Schätzer für das Prognoserisiko herangezogen wird. Eine Handelsstrategie auf Basis der Prognosen wirft unter Risiko-Varianz Gesichtspunkten höhere Renditen ab als eine Buy and Hold oder eine auf gleitenden Durchschnitten basierende Strategie
Keywords: C53; C45; C43; G12; 330; initial public offerings; neural networks; stock market index; cointegration analysis